Analysis of Slope Stability in Embankment Areas 'Shaiful Dump' at PT Agincourt Resources, North Sumatra - Okky Chandra Perdana; Barlian Dwinagara; S Koesnaryo; Saptono Singgih (Postgraduate School, Universitas Negeri Padang, 2023)
The safety factor from the stability of a slope is one of the important things that must be considered, especially in open pit mine planning such as the system implemented by PT Agincourt Resource. Research on the